The role of thymus- and extrathymus-derived regulatory T cells in maternal-fetal tolerance - Li, Zhengjuan; Liang, Xinyuan; Chen, Xiaowen; Chen, Yuying; Wang, Fang; Wang, Shuoshi; Liao, Yihong; Li, Liping (Frontiers in Immunology, 2023)
Regulatory T (Treg) cells could be divided into thymus-derived Treg (tTreg) cells and peripherally derived Treg (pTreg) cells, and in vitro induced Treg (iTreg) cells. To date, the functions of tTreg versus pTreg and their relative contributions to maternal-fetal immune tolerance remain insufficiently defined due to a lack of a specific marker to distinguish tTreg cells from pTreg cells. In this study, we investigated the role of thymus- and extrathymus-derived Treg cells in pregnancy tolerance using transgenic ACT-mOVA, Foxp3DTR and Foxp3GFP mice, and Treg cell adoptive transfer, etc. We found that the frequencies of Treg cells in the thymus, spleen and lymph nodes (LNs) in either syngeneically- or allogeneically-mated pregnant mice were not different from non-pregnant mice. However, percentages of blood Treg cells in pregnant mice increased at mid-gestation, and percentages of decidua Treg cells in pregnant mice increased as the pregnancy progressed compared with non-pregnant mice, and were significantly higher in allogeneic mice than those in syngeneic group. Compared with syngeneic mice, levels of CCR2 and CCR6 on blood and decidua Treg cells and CCL12 in the decidua significantly increased in allogeneic mice. A surrogate fetal antigen mOVA that was recognized by naïve T cells from OT-IIFoxp3GFP mice induced the generation of pTreg cells in vivo. Transfusion of thymus and spleen Treg cells significantly decreased diphtheria toxin (DT)-increased embryo resorption rates (ERRs) and IFN-γ levels in the blood and decidua. iTreg cells also decreased ERRs and IFN-γ levels in the blood and decidua to an extent lower than thymus and spleen Treg cells. In conclusion, increased blood and decidua Treg cells in pregnancy and increased ERRs in DT-treated Foxp3DTR mice suggest an important immunosuppressive role of Treg cells in pregnancy. Elevated decidua Treg cells in pregnancy could be derived from the recruitment of tTreg cells to the decidua, or from the transformation of naïve T cells in the decidua to pTreg cells. While the immune-suppression effects of thymus and spleen Treg cells are comparable, iTreg cells might play a weaker role in maternal-fetal tolerance.